Thalassaemia: a study on the perception of patients and family members - Jantan, Abdul Wahab; Muhammad, Siti Aeshah @ Naznin; Mat Zain, Nora; Abdul Rahman, Suzanah; Mohamed Yusop, Zulaiha; Abdul Rahim, Aidil Faszrul; Wan Su, Kamaruzaman (2011)
Significant advances in the clinical management of thalassaemia has generally led to improved survival and quality of life. This development however has not been matched by progress in the psychosocial rehabilitation. As such thalassaemia continues to pose challenges to patients and their family members. Very few studies have been carried out in Malaysia thus far in relation to psychosocial aspects of thalassaemia patients and their immediate family members. Findings of studies conducted elsewhere may not reflect the true picture in Malaysia.